Balanced Metric and Berezin Quantization on the Siegel-Jacobi Ball - Berceanu, S. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We determine the matrix of the balanced metric of the Siegel-Jacobi ball and its inverse. We calculate the scalar curvature, the Ricci form and the Laplace-Beltrami operator of this manifold. We discuss several geometric aspects related with Berezin quantization on the Siegel-Jacobi ball.